A holistic framework for patient experience: 5P model - Ozcelik, Ayse Bengi; Varnali, Kaan; Burnaz, Sebnem (Emerald Group Publishing Ltd, 2021)
Purpose Hospitals have become competitive organizations striving to serve the needs of empowered consumers seeking positive experiences. As a result, the patient experience turns into a critical driver of performance for hospitals. Accordingly, the question what are the critical dimensions for creating a well-designed patient experience? has been drawing increasing attention from the industry and academia alike. This paper aims to contribute to the understanding of patient experience by using multiple source data obtained from experts and patients. Design/methodology/approach This study uses a qualitative research approach to examine the perspectives of both health-care experts and patients about the experience. A semi-structured interview series is conducted with health-care professionals, academicians, researchers, physicians and patients. Findings The results suggest a novel framework for the patient experience including five critical dimensions as follows: provider, physician, patient, personnel and periphery. This framework, 5Ps of patient experience, provides a holistic picture, which integrates the perspectives of patients, health-care providers and experts including scholars and researchers. Practical implications The 5P framework can be used by health-care professionals to better understand the driving factors of patient experience and to create a strategy to improve patient satisfaction. Originality/value To the best of the authors' knowledge, the present study is the first qualitative study, which provides a holistic approach to patient experience independent from the branch and considers the perspectives of both health-care experts and patients.
Keywords: Customer Experience; Health-Care Marketing; Health-Care Management; Patient Experience; Patient İnteraction; Health-Care; Service Quality; Satisfaction; Hospitals; Systems; Communication; Perceptions; Performance; Environment; Improve